Collaboration and management techniques for the expansion of small and medium-sized enterprises (SME) contractors in Cape Coast Metropolis, Ghana / Zakari Mustapha, Benjamin Boahene Akomah and Chris Kurbom Tieru - Mustapha, Zakari; Akomah, Benjamin Boahene; Tieru, Chris Kurbom (UiTM Press, 2024)
The construction industry, spearheaded by small and medium-sized enterprises (SMEs), plays a vital role in economic development and poverty alleviation. Yet, numerous SME contractors need help to expand, hindering their potential contribution. To address this critical gap, this study explored the factors influencing building contractors' growth in Ghana's Cape Coast Metropolis. A targeted questionnaire survey of one hundred and twenty-one (121) building and civil engineering contractors was employed to examine the interplay between two (2) key determinants of growth: building stable teamwork and implementing proper management systems. The analysis revealed six (6) crucial factors, three (3) within each category, that demonstrably drive contractor expansion in the Cape Coast Metropolis. These factors encompass fostering team cohesion through training, recognition, effective collaboration, strategic project differentiation, prioritising project management, and proactive risk mitigation. The study's findings underscore the critical importance of internal (teamwork) and external (management systems) factors in propelling SME contractor growth within this context. Equipping policymakers and stakeholders with this actionable knowledge will pave the way for targeted interventions and policy initiatives. These initiatives can empower building contractors with the necessary skills and support systems to overcome growth barriers, unlock their full potential, and contribute more significantly to the economic prosperity of Cape Coast Metropolis and beyond.